Ceramic petrography, mineralogy and typology of eneolithic pottery from Krašnja, Slovenia - Žibrat Gašparič, Andreja (Documenta Praehistorica, 2014)
In this article, we present newly excavated Eneolithic pottery from the site at Krašnja near Lukovica in central Slovenia. The material was AMS 14 C dated and is contemporaneous with archaeological sites from the Ljubljansko barje region in Slovenia. The vessels were reconstructed and then various types of pots, dishes, cups, and beakers were analysed using petrography and the X-ray diffraction method. Additionally, the clay remains of walls and the floor of an Eneolithic kiln excavated at the site were also analysed. The results show that Eneolithic potters used different fabrics to make vessels, and mostly one recipe with added calcite. The raw source material probably came from a nearby valley to the south of the site at Krašnja.
Keywords: ceramic; datiranje; keramika; Krašnja; lončevina; Lukovica; Lukovica pri Domžalah; neolitik; posode; prazgodovina; Slovenia; Slovenija